Ordinary genius : the story of Albert Einstein - McPherson, Stephanie Sammartino (Minneapolis : Carolrhoda Books, 1995)
Recounts the life of the scientist whose theories of relativity revolutionized the way we look at space and time.
Includes bibliographical references (p. 92-93) and index.
Wilson's Children
Wilson's Junior High School
Elem. School Library Collection
4.8
3-6
Keywords: Einstein, Albert, -- 1879-1955 -- Juvenile literature; Physicists -- Biography -- Juvenile literature; Einstein, Albert, -- 1879-1955.; Physicists; Einstein, Albert, -- 1879-1955.; Physicists -- Biography